2001
DOI: 10.1034/j.1600-0501.2001.120614.x
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic elasticity of cortical and cancellous bone in the posterior mandible increases peri‐implant stress and strain under oblique loading

Abstract: The aim of this study was to compare implant-bone interface stresses and peri-implant principal strains in anisotropic versus isotropic three-dimensional finite element models of an osseointegrated implant in the posterior mandible. We obtained anisotropic (transversely isotropic) elastic constants for mandibular bone and derived equivalent isotropic constants by averaging over all possible spatial orientations. A finite element model was constructed using ten-node tetrahedral p-elements, providing curved edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(137 citation statements)
references
References 32 publications
6
123
0
4
Order By: Relevance
“…Numerous other studies corroborate the anisotropic behaviour of bone, see some examples in Nordin and Frankel (2001), O'Mahony et al (2001), and Vercher et al (2014).…”
Section: Fe Assuming Anisotropic Behavioursupporting
confidence: 55%
“…Numerous other studies corroborate the anisotropic behaviour of bone, see some examples in Nordin and Frankel (2001), O'Mahony et al (2001), and Vercher et al (2014).…”
Section: Fe Assuming Anisotropic Behavioursupporting
confidence: 55%
“…The analysis was done in the linear elastic range with total adherence between the parts. A non-linear solution with contacts better mimics realistic behavior, however, the results strongly depend on mesh quality on contacting interfaces, as also frictional condition which is not congruent in studies [20,21]. In specific range an increase of the stress in bone tissue around the implants is influenced by anisotropic values of the bone [22], however, in most works because of the problems with orienting of the coordinating system around the alveolar processes are used linear isotropic models for bone tissues behavior [13,23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the thickness of the cortical bone is not the same everywhere in the mandible. It has been shown that the elastic properties of bones are anisotropic [39][40]. However, elasticity is often considered as isotropic in the FE model of implants in the mandible [41][42][43][44], and it has been shown that the impact of anisotropy on the stress state into a bone is limited, with a maximal difference lower than 10 % [45].…”
Section: Bone Materials Characteristicsmentioning
confidence: 99%